Imaging features of the evolving patterns of metastatic prostate cancer. Issue 2 (February 2022) - Curcean, A.; Curcean, S.; Rescigno, P.; Dafydd, D. ap; Tree, A.; Reid, A.; Koh, D.-M.; Sohaib, A.; Tunariu, N.; Shur, J.
Abstract : The pattern of metastases in prostate cancer (PC) is evolving. Increased use of imaging, newer imaging techniques with higher sensitivity for disease detection and patients receiving multiple lines of novel therapies with increased life expectancy are likely to be contributory. Awareness of metastatic disease patterns improves early diagnosis, accurate staging, and initiation of appropriate therapy, and can inform prognostic information and anticipate potential disease complications. The aim of this review is to document the spectrum of metastases in PC including emerging and unusual patterns, and to highlight the role of novel imaging including prostate-specific membrane antigen (PSMA)-positron-emission tomography (PET) and whole-body magnetic resonance imaging (WB-MRI) to improve diagnostic and response assessment accuracy.